Anatomy of Bursa of Fabricius of Pati duck (Anas platyrhynchos domesticus) of Assam at Different Stages of Development - Deka, A.; Mahanta, J. D.; Perumal, P. (International Journal of Bio-resource and Stress Management, 2020)
The present investigation was conducted on the histomorphological, histo-chemical and scanning electron microscopical observation on the Bursa of Pati duck of Assam at different stages of development. The experiment was conducted from 2017 to 2019. In current study, the Bursa of Fabricius was observed at 1st week of age of Pati duck and underwent atrophy at 24th week of age. The Bursa of Fabricius was found at the dorsal aspect of the Proctodeum. The length, breadth, thickness and weight of Bursa of Fabricius showed increasing trend from 1st week to 16th week of age of Pati duck. Histological, the folds of Bursa of Fabricius contained numerous polyhedral shaped lymphoid follicles at the lamina propria and it was composed of outer cortex and inner medulla. A layer of undifferentiated epithelial cells occupied at the periphery of the medulla, which was separated from the cortex by a capillary layer. Histochemicaly, the undifferentiated epithelial cell of lymphoid follicle of Bursa of Fabricius was showing strong reaction for acid phosphatase and adenosine triphosphatase. In scanning electron microscope, the Bursal folds of Bursa of Fabricius contained lining epithelium and lymphoid follicle. This follicle contained numerous lymphocytes along with connective tissue fibers. The Bursal follicle was situated in lamina propria of Bursal folds. Lamina propria and interfollicular area also contained connective tissue fibers.